Pre-exposure Prophylaxis Adherence Among Men Who Have Sex With Men: A Systematic Review and Meta-analysis - Suchitra Hudrudchai; Charin Suwanwong; Pitchada Prasittichok; Kanu Priya Mohan; Nopphadol Janeaim (Korean Society for Preventive Medicine, 2024)
Objectives: The effectiveness and efficiency of pre-exposure prophylaxis (PrEP) in reducing the transmission of human immunodeficiency virus (HIV) among men who have sex with men (MSM) relies on how widely it is adopted and adhered to, particularly among high-risk groups of MSM. The meta-analysis aimed to collect and analyze existing evidence on various factors related to PrEP adherence in MSM, including demographic characteristics, sexual behaviors, substance use, and psychosocial factors. Methods: The meta-analysis followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The search included articles published between January 2018 and December 2022, obtained from the PubMed, ScienceDirect, and Scopus databases. The studies that were included in the analysis reported the proportion of MSM who demonstrated adherence to PrEP and underwent quality appraisal using the Newcastle-Ottawa Scale. Results: Of the 268 studies initially identified, only 12 met the inclusion criteria and were included in the final meta-analysis. The findings indicated that education (odds ratio [OR], 1.64; 95% confidence interval [CI], 1.12 to 2.40), number of sexual partners (OR, 1.16; 95% CI, 1.02 to 1.31), engaging in sexual activities with an human immunodeficiency virus-positive partner (OR, 1.59; 95% CI, 1.16 to 2.26), substance use (OR, 0.83; 95% CI, 0.70 to 0.99), and lower levels of depression (OR, 0.55; 95% CI, 0.37 to 0.82) were associated with higher rates of PrEP adherence among MSM. Conclusions: Despite these findings, further research is necessary to investigate PrEP adherence more comprehensively. The findings of this meta-analysis can be utilized to inform interventions aimed at improving PrEP adherence among MSM and provide directions for future research in this area.